The European Convention on Human Rights : collected essays - Loukaidēs, Loukēs G. (Nijhoff law specials, 2007)
Comprises of 12 articles on topics drawn from the European Convention on Human Rights. This book examines topics from a critical standpoint and some important judgments of the European Court of Human Rights are taken to task.